The Extremes of Disturbance Reduce Functional Redundancy: Functional Trait Assessment of the Shallow Antarctic Benthos - Robinson, Ben J. O.; Barnes, David K. A.; Grange, Laura J.; Morley, Simon A. (Frontiers in Marine Science, 2022)
Climate-driven changes in disturbance are a major threat to ecosystem Functional diversity. The selective mechanisms underlying ecosystem response to disturbance are far from universal and remain the subject of scientific debate. Ice scouring of the shallow Antarctic benthos is one of the largest disturbance gradients in the natural environment and thus provides an opportunity to investigate how disturbance gradients influence functional structure of a biological assemblage. The Western Antarctic Peninsula, in particular, is a hotspot of climate-driven environmental change. Addressing how this system might respond to species loss is critical. Previous surveys across the shallowest 100 m of the seabed, detected unimodal changes in diversity and a shift in assemblage composition in response to disturbance gradients. This study investigated how functional traits and associated functional diversity change across the depth gradient. Our results revealed that selective mechanisms, such as disturbance filtering and inter-species competition, reduce functional redundancy at the extremes of the disturbance gradient. Our study highlights areas of potential vulnerability to future environmental change due to low functional redundancy. Threatening the important negative (mitigating) feedbacks on climate change, through blue carbon, currently provided by Antarctic continental shelf benthic assemblages.